Bioconversion of inorganic selenium to less toxic selenium forms by microbes: A review - Nie, Xinling; Yang, Xurui; He, Junyi; Liu, Pei; Shi, Hao; Wang, Tao; Zhang, Daihui (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, inorganic selenium conversion to organic form by microbes has attracted much attention. Compared to other microbes, yeast is an ideal source for producing organic selenium. With the improvement of scientific awareness and the continuous progress of nanotechnology, selenium nanoparticles can not only play the unique functions of organic selenium and inorganic selenium but also have higher safety, absorption and biological activity than other selenium forms. Therefore, the focus of attention has gradually shifted beyond the level of selenium enrichment in yeast to the combination of biosynthetic selenium nanoparticles (BioSeNPs). This paper primarily reviews inorganic selenium and its conversion to less toxic organic selenium and BioSeNPs by microbes. The synthesis method and potential mechanism of organic selenium and BioSeNPs are also introduced, which provide a basis for the production of specific forms of selenium. The methods to characterize selenium in different forms are discussed to understand the morphology, size and other characteristics of selenium. In general, to obtain safer and higher selenium content products, it is necessary to develop yeast resources with higher selenium conversion and accumulation.